One-dimensional thermal shock problem for a semi-infinite hygrothermoelastic rod - Ailawalia, Praveen; Kumar, Lalit (Zielona Góra: Uniwersytet Zielonogórski)
The present research article deals with the study of a boundary value problem of a one-dimensional semi-infinite hygro-thermoelastic rod of length l. The deformation of the rod is under consideration when the left boundary of the hygro-thermoelastic rod is subjected to a sudden heat source. The solutions of the considered variables are decomposed in terms of normal modes.
Keywords: one-dimensional; heat source; temperature distribution; hygrothermoelastic rod; moisture concentration